Preserving our heritage perspectives from antiquity to the digital age - Cloonan, Micháele Valerie 1955- (London Facet Publishing, 2015)
A collection of key introductory readings of historic preservation literature. Since the essays are presented in an historical timeline, the reader discovers the roots of many current debates. By bringing together material from a variety of sources, this text represents the depth and scope of this intellectually rich field.
Early perspectives on preservation -- Perspectives on cultural heritage -- Preservation in context: libraries, archives, museums, and the built environment -- Collections: development and management -- Risks to cultural heritage: time, nature, and people -- Conservation -- Frameworks for digital preservation -- Preservation policy -- Ethics and values -- Multicultural perspectives -- Sustainability.
Includes bibliographical references and indexes.
Keywords: Library materials -- Conservation and restoration; Books -- Conservation and restoration; Archival materials -- Conservation and restoration; Manuscripts -- Conservation and restoration; Sound recordings -- Conservation and restoration; Photographs -- Conservation and restoration; Motion picture film -- Preservation; Digital preservation; Museums -- Conservation and restoration; Cultural property -- Conservation and restoration